Character Education for University Student from Psychological Perspective in the Era of Globalization and Multiculturalism - Muhammad Awin Alaby (CV. Bunda Ratu, 2023)
Character education is one of the ways to apply values that reflect our nation’s identity and culture to create a foundation for the students’ character. In the era of globalization and multiculturalism, new challenges arise that hinder the people’s character development, which is the erosion of national identity by foreign culture and the threat to intercultural intolerance. This study is a literature review on the issue of students’ character education in the era of globalization and multiculturalism from the perspective of psychology. Character education is imperative to be done in the era of globalization to preserve students’ national identity. This character education is expected to facilitate character reinforcement in students without sacrificing the positive impacts of globalization. One of the ways to achieve this is by multiple acculturations where students battle their arguments and perspectives so that they can comprehend and respect each other’s perspectives and opinions to achieve mutual understanding and respect of each other perspectives that are affected by ethnicities, beliefs, and cultures. Educators as the main individual responsible for character education can implement control management to internalize the national values in students optimally.